Cytotoxicity of Triple Antibiotic Paste and Calcium Hydroxide against Cultured Human Dental Pulp Fibroblasts - Hosseini Matin, Marjan; Zare Jahromi, Maryam; Fesharaki, Mehrafarin; Ostad Sharif, Maryam (Journal of Dental School, 2019)
Objective: In necrotic immature teeth, intra canal medicaments such as triple antibiotic paste (TAP) and calcium hydroxide (CH) are used for root canal disinfection and regeneration treatment. However, the effect of these medicaments on dental pulp fibroblasts has yet to be known. This study aimed to assess the cytotoxicity of CH and TAP against cultured human dental pulp fibroblasts (HDPFs) obtained from third molars. Methods: In this in vitro study, fibroblasts were obtained from the dental pulp of two third molars. Fibroblasts were exposed to 0.1, 1 and 10 mg/mL concentrations of TAP and CH. Six samples were prepared of each medicament and fibroblast viability was evaluated after 72 hours. Data were analyzed using one-way and two-way ANOVA (p<0.001). The percentage of cell viability was calculated and the cytotoxicity of the medicament was categorized as severe (30%), moderate (30- 60%), mild (60-90%) and non-toxic (>90%). Results: In TAP samples, only the 10 mg/mL concentration had a significant difference with the control group in terms of the percentage of cell viability and showed moderate cytotoxicity. In CH samples, the 1 and 10 mg/mL concentrations showed significant differences with the control group and were severely cytotoxic. Conclusion: Reduction in cell viability of fibroblasts by increase in concentration was significantly greater in CH compared to TAP group. Thus, in regeneration treatments, these medicaments must be used in concentrations with adequate therapeutic and insignificant adverse effects on fibroblasts.